Allocation of risk factors for geodetic tasks in construction schedules - Kowacka Magdalena (De Gruyter, 2021)
Road construction projects are characterized by multitasking and the influence of the correct implementation of one task on another. In the subject literature, we can encounter the analysis of risk factors throughout the project, and yet, we rarely find the distinction and characteristics of the impact of risk factors resulting from the implementation of planning and measurement tasks, the correctness and timeliness that have a huge impact on the performance of subsequent tasks, and the success of the project. Additionally, attention should be paid on the distinction between design work and the implementation of construction. During the implementation of construction works, we are more capable of detecting errors faster at the initial stage than at the stage of performing measurements, which suggests the need to focus on minimizing the occurrence of risk factors at the initial stage. Therefore, two questions have been asked. How to quantify the risk factors of geodetic works in road construction projects? How to allocate quantified risk factors of geodetic works in the schedule? The following article presents the description and the example of the practical use of the risk assessment procedure of geodetic works and risk allocation in the schedule based on the MORAG method (Method of Risk Analysis for Geodesy), which is the original method of risk analysis of geodetic works in road construction projects. As a result of these works, the risk values for the i-th risk factor and i-th geodetic task were determined, considering the increase in the duration of the work, the increase in the costs of the work, and all evaluation criteria. Then, the extension was described and calculated based on the data obtained from the actual implementation of the road construction project, the value, which in this case is 11.05 days, was entered into the modified schedule. The results of this study may help to better understand the scale of the impact of the correctness of the implementation of geodesy tasks on the implementation of construction tasks. Additionally, they may serve to increase the awareness of the scale of consequences of incorrectly performed measurement tasks (demolition is necessary) and greater attention on the cooperation between the entities implementing these activities.